THE USE OF FAIES (FIRST AID IN ENGLISH SYSTEM) METHOD TO DEVELOP THE STUDENTS’ WRITING ABILITY - Abd Rajab; Rahmiani Rahmiani (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2013)
This research aimed to find out the improvement of the students’ writing ability in term of grammar covering simple past tense and past continuous tense and vocabulary covering verb and noun, especially in recount text at the eighth-grade students of SMP Unismuh Makassar. The researcher used a classroom action research (CAR) which was conducted in two cycles where each cycle consisted of four meetings and the application consisted of four steps namely planning, action, observation, and reflection. The technique of collecting data is writing test and observation and technique of data analysis is quantitative. The number of the research subject was 26 students in class VIIIB and all the students were male. The research findings indicated that using FAIES method could improve the students writing ability in terms of grammar and vocabulary. It was proved by the students’ mean score in the test of cycle II, the result was (75.25) which increased 15.15 % from the cycle I mean score (60.1). It was highly increased from a diagnostic test (D – test) mean score (48.2). The students’ achievement in cycle II indicated that it had met the researcher score target (75) where the classification of students’ score was 4 students got excellent score where the percentage was 15.4%, 11 students got good score where the percentage was 42.3%, 10 students got fair score where the percentage was 38.5% and 1 student got poor score where the percentage was 3.8%. Based on the findings of the research above, the researcher concluded that FAIES method were successful in improving the students’ writing ability covering grammar and vocabulary for recount text at the eighth-grade students of SMP Unismuh Makassar class VIIIB .Keyword: FAIES, develop, writing, ability